The Pretenses of Loyalty: Locke, Liberal Theory, and American Political Theology. By John Perry - Cowan, David (The journal of theological studies, 2013)
The author Salman Rushdie, famously sent into hiding due to a fatwa, once quipped ‘No, I don’t think it’s fair to label Islam “violent.” But I will say that to my knowledge, no writer has ever gone into hiding for criticizing the Amish.’ Rushdie’s comment is another iteration of the long-running boundary dispute between religion and state and it is easy to think of Rushdie as the poster child for religious toleration before 9/11; but equally, could his statement imply that the Amish are simply being good American Lockeans, faithful to the founding fathers’ sense of Lockean toleration? It is this question of toleration, and to whom we owe loyalty, chiefly in the American context, which is given an insightful and careful assessment by John Perry.